2014
DOI: 10.1186/1742-4690-11-23
|View full text |Cite
|
Sign up to set email alerts
|

A novel HIV-1-encoded microRNA enhances its viral replication by targeting the TATA box region

Abstract: BackgroundA lot of microRNAs (miRNAs) derived from viral genomes have been identified. Many of them play various important roles in virus replication and virus-host interaction. Cellular miRNAs have been shown to participate in the regulation of HIV-1 viral replication, while the role of viral-encoded miRNAs in this process is largely unknown.ResultsIn this report, through a strategy combining computational prediction and deep sequencing, we identified a novel HIV-1-encoded miRNA, miR-H3. MiR-H3 locates in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 75 publications
3
91
0
1
Order By: Relevance
“…Although some reports suggest that noncoding RNAs derived from the promoter region are the mediator of small RNA-induced chromatin epigenetic modifications (Schwartz et al 2008;Napoli et al 2009;Chu et al 2010), the attempt to find IL-2 promoter-associated noncoding transcript did not get any positive signal of them and overexpression of the speculated paRNA did not affect IL-2 promoter activity either in our study. Thus, our findings reveal a novel transcription activation approach which is through the direct interaction between miRNAs and the core transcription machinery (Zhang et al 2014). A recent report suggested that the key protein components of RNAi pathway, i.e., DICER2 and AGO2, are associated with RNA Pol II core transcription machinery (Cernilogar et al 2011), while our study further reveals that cellular miRNAs could directly interact with the core promoters.…”
Section: Cellular Mirnas Targeting Tata-box Motif Up-regulate the Prosupporting
confidence: 56%
See 3 more Smart Citations
“…Although some reports suggest that noncoding RNAs derived from the promoter region are the mediator of small RNA-induced chromatin epigenetic modifications (Schwartz et al 2008;Napoli et al 2009;Chu et al 2010), the attempt to find IL-2 promoter-associated noncoding transcript did not get any positive signal of them and overexpression of the speculated paRNA did not affect IL-2 promoter activity either in our study. Thus, our findings reveal a novel transcription activation approach which is through the direct interaction between miRNAs and the core transcription machinery (Zhang et al 2014). A recent report suggested that the key protein components of RNAi pathway, i.e., DICER2 and AGO2, are associated with RNA Pol II core transcription machinery (Cernilogar et al 2011), while our study further reveals that cellular miRNAs could directly interact with the core promoters.…”
Section: Cellular Mirnas Targeting Tata-box Motif Up-regulate the Prosupporting
confidence: 56%
“…Unlike previous studies of the small RNAs (miRNAs or siRNAs) induced gene expression activation (a phenomenon named RNAa) (Li et al 2006;Janowski et al 2007;Place et al 2008), the miRNA target sites of the present work and the HIV-1-encoded miRNA miR-H3 (Zhang et al 2014) are quite unique and within 50 bp upstream of the TSS. Moreover, these miRNAs and their binding proteins AGO1 and AGO2 are associated with the general transcription factors such as Pol II and TBP, suggesting an interaction between the "nuclear RISC" and the RNA Pol II core transcription machinery.…”
Section: Cellular Mirnas Targeting Tata-box Motif Up-regulate the Promentioning
confidence: 72%
See 2 more Smart Citations
“…Despite the theoretical barriers preventing RNA viruses from encoding miRNAs, recent studies have confirmed that laboratory-engineered RNA viruses, including the influenza virus, sindbis virus, and vesicular stomatitis virus (VSV), are capable of expressing miRNA-like small RNAs [2025]. Furthermore, a few retroviruses, including the human immunodeficiency virus (HIV) [26,27], bovine leukemia virus (BLV) [28,29] and three cytoplasmic RNA viruses, the West Nile virus (WNV) [30], Dengue virus (DENV) [31] and hepatitis A virus (HAV) [20], were found to encode miRNAs, although the underlying mechanisms remain unclear.…”
mentioning
confidence: 99%